Glacial geomorphology and Pleistocene glacier reconstruction in the Demänovská Valley, Low Tatra Mountains, Slovakia - Pyrda, Agata (Geology, Geophysics and Environment, 2023)
In the Western Carpathians, clear evidence of the Pleistocene glaciations only occurs in two mountain massifs – the Tatra and Low Tatra Mountains. The Low Tatra Mountains (2043 m a.s.l.), contrary to the higher and more strongly glaciated Tatra Mountains (2654 m a.s.l.), have previously been much less attractive for scientific research. Hence, in these mountains, both glacial landforms and chronology, together with a detailed reconstruction of glacier geometry and resulted equilibrium line altitude (ELA), are poorly documented. The aim of this paper is to characterize the glacial relief and reconstruction of geometry and ELA of the Zadná voda glacier in the Demänovská Valley system which belongs to the category of the largest Pleistocene glaciers on the northern slope of the Low Tatra Mountains. The mapping results show that a freshly shaped, massive terminal moraine of maximal ice extent (MIE, likely formed during the global Last Glacial Maximum – LGM) occurs 4.3 km distance down-valley from the glacial cirque backwalls. There is no evidence of deposits from older glaciations beyond the terminal moraine down the valley. The terminal zone of the MIE features a fresh morainic landscape with hummocky topography with kettle hollows and the only known morainic lake in the Low Tatra Mountains – Vrbické pleso. During the MIE, the Zadná voda glacier covered 7 km2 of the area and featured a mean thickness of 48 m. The ELA of this glacier was 1433 m, determined by the area-altitude balance ratio (AABR) 1.6 method, which is a similar value to the LGM ELA calculated in the Western Tatra Mountains. The recessional stages were only recognized in the cirques area, where one or two generations of debris-covered glaciers and rock glaciers mark the final deglaciation of the study area.